Effect of Thyme and Garlic Aromatic Waters on Microbiological Properties of Raw Milk Cheese - Sagdic, Osman; Cankurt, Hasan; Tornuk, Fatih; Arici, Muhammet (UNIV NAMIK KEMAL, 2017)
In the present study, it was aimed to investigate the effect of brine solutions containing thyme and garlic extracts on physicochemical, microbiological and textural properties of Turkish white cheese made from raw milk during ripening. For this aim, garlic aromatic water (GAW), thyme hydrosol (TH) or their mixture (1:1 v/v) were incorporated into the brine with different salt concentrations (10%, 13% and 16%) at the ratio of 10% and used in the cheese ripening for 90 days. Addition of TH and GAW into the brine caused higher acidity and lower pH values while increase in salt level resulted in higher dry matter (DM) of cheese. Counts of total mesophilic aerobic bacteria (TMAB), yeast-mold (YM), lactoccocci and lactobacilli were fluctuatingly influenced from brine combinations while coagulase positive staphylococci was completely inhibited during the ripening. In general, TH, GAW or their mixture increased hardness, gumminess and chewiness of the cheese at the 1st day while cohesiveness, resilience and springiness values were not significantly (P>0.05) affected.
Keywords: White cheese; ripening; garlic; thyme; aromatic water; LISTERIA-MONOCYTOGENES; SENSORY CHARACTERISTICS; STAPHYLOCOCCUS-AUREUS; QUALITY; MANUFACTURE; VARIETIES; TURKEY; FATE; TIME; Agriculture